(untitled) (Research, Society and Development, 2023)
This study aimed to analyze international and national production regarding educational programs for couples. To this end we conducted a systematic literature review using the following databases: PubMed, APA, LILACS and ERIC. We followed the PRISMA method. The results showed that it was only possible to identify programs on the theme in the international context, with emphasis on American research. Moreover, it is possible to state that studies involving educational programs for couples continue to be centered on a relatively homogeneous population, that is, young and heterosexual couples. Most present among the programs used were the Prevention Relationship Enhancement Program (PREP) and OurRelationship (OuR). Studies with mediators showed communication to be an important mechanism for change, while studies with moderators highlighted relational and individual risk factors. Both communication and satisfaction were the most used outcomes for efficacy studies. In the Brazilian context, however, no studies with a control group were found. We discuss the need for more studies with educational programs for couples in the Brazilian context.